Regional Wage Inequality in Egypt: Relationships to Micro and Macro Indicators - Mostafa, Noha (AUC Knowledge Fountain, 2021)
Addressing regional disparities in Egypt is of paramount importance for the country’s success in achieving the pillars of its 2030 strategy, as well as the Sustainable Development Goals (SDGs). This paper focuses on examining regional disparities in wages, not only in relation to the micro level characteristics of workers such as their level of educational attainment and acquired experience, but also with regard to the overall economic conditions of the region where they work. The paper compiled a novel dataset of Egypt’s governorates macroeconomic indicators that includes the shares of public investment funds, poverty and unemployment rates and analyzed the evolution of such indicators over the period (2008-2018). The second contribution of this paper was to estimate a Mincer wage equation for each region, using micro data from the last two rounds of the ELMPS, in addition to the analyzed macro-economic variables in the years 2012 and 2018. Moreover, the corrected regional wage gaps were estimated. To the best of the author’s knowledge, the inclusion of macro-level indicators into the Mincer wage equation was never empirically investigated in the Egyptian labor market. The results of the econometric estimation provided evidence for the significant impact of both poverty and public investments’ shares on the real hourly wage rate prevailing in Egypt’s different regions. In addition, the estimated returns to the different educational levels significantly differed from one region to another. The paper concluded by suggesting several policies that could help mitigate regional wage disparities in the lagging regions